Orange Data Mining Integration Improves Database Learning Scores in High School: Integrasi Penambangan Data Orange Meningkatkan Skor Pembelajaran Database di Sekolah Menengah Atas - Santoso, Dian Rahma; Yunanto, Angga; Affandi, Aditya Krisna; Pamungkasari, Silvana Desy (Indonesian Journal of Innovation Studies, 2026)
General Background: Database learning is a fundamental component of information technology education that requires both conceptual understanding and practical abilities such as designing relational database structures and writing accurate SQL queries. Specific Background: In many classroom settings, students struggle to understand database concepts because learning methods often rely on conventional instruction with limited variation and minimal technological support. Knowledge Gap: Although interactive learning tools and data visualization software have been suggested as alternatives, empirical classroom-based evidence regarding their use in database instruction at the secondary school level remains limited. Aims: This study investigates whether the integration of interactive learning modules with Orange Data Mining software is associated with measurable changes in database learning outcomes among Grade 11 students at SMAN 3 Sidoarjo. Results: Using a quantitative pre-test–post-test design involving 20 students, descriptive statistics showed an increase in mean scores from 76.50 in the pre-test to 83.30 in the post-test. Normality testing confirmed normally distributed data, and a paired sample t-test produced a significance value of 0.011 (<0.05), indicating a statistically significant difference between the two measurements. Novelty: The study demonstrates a classroom implementation in which interactive modules are combined with visual data mining tools to support both conceptual comprehension and practical data analysis activities in database learning. Implications: These findings provide empirical evidence supporting the integration of data visualization–based learning environments in secondary information technology education and suggest that technology-supported instructional strategies may contribute to improved database learning performance and student engagement. Highlights: Mean student performance increased from 76.50 before treatment to 83.30 afterward. Statistical testing showed a significant difference between pre-test and post-test results (p = 0.011). Visual data exploration activities helped learners interpret relational data patterns and query results more clearly. Keywords: Orange Data Mining, Interactive Learning Media, Online Learning, Data Analysis.